Clostridium septicum arthritis in a young infant: A case report. (June 2019) - Grover, Pragati; Bala, Kiran; Muralidharan, Jayashree; Angrup, Archana; Ray, Pallab
Abstract: Septic arthritis is one of the most serious conditions leading to grave consequences in all age groups, with a number of cases seen in infancy and childhood. Although septic arthritis in neonates is a known clinical entity, it is a diagnostic dilemma for the paediatricians. Of the reported causes of bacterial arthritis, anaerobic bacteria account for only 1%. Anaerobic bacterial septic arthritis may be more common than appreciated and therefore anaerobic as well as aerobic cultures should be done in all cases of septic arthritis. We report the first documented case of spontaneous septic arthritis due to Clostridium septicum in an infant with successful outcome. Highlights: Diagnosis of septic arthritis in the paediatric age group is a dilemma for the paediatricians. Clostridium septicum is a rare cause of septic arthritis in this age group. In every case of septic arthritis anaerobic etiology should be considered. Identification to species level and appropriate treatment of Clostridial arthritis has a favourable outcome.